Digital world Englishes - Friedrich, Patricia (Routledge, 2025)
"World Englishes Online aims to be an introduction to and exposition of the universe of world Englishes as represented in online spaces. It presents aspects of world Englishes theory in relation to our evolving digital reality and examples of authentic language variation, change and code-mixing. To do that, it visits such stations as world Englishes frameworks, pedagogy, new media, augmented intelligence, interactions with other languages, research methodology, and Internet user identities. The reader of the book will come away from the reading with a clear idea of what world Englishes are and how they have morphed, adapted, and come to manifest in online environments. This is likely the first book-length treatment of this topic from the lenses of linguistic creativity, morphing identities, and the power of languages of wider communication"-- Provided by publisher.
Keywords: English language -- Variation.; Language and the Internet.; elektronické knihy; electronic books